2011
DOI: 10.1007/s00248-011-9939-z
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Changes Elicited by Exposure to Cyanobacterial Allelochemicals

Abstract: An increasing body of evidence points out that allelopathy may be an important process shaping microbial communities in aquatic ecosystems. Cyanobacteria have well-documented allelopathic properties, mainly derived from the evaluation of the activity of allelopathic extracts or pure compounds towards monocultures of selected target microorganisms. Consequently, little is known regarding the community dynamics of microorganisms associated with allelopathic interactions. In this laboratory-based study, a Microcy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 39 publications
3
26
0
1
Order By: Relevance
“…Second, food intake and digestion rates affect the speed of food passage through the gut and thus the rate at which microbes are lost via excretion. Third, colonist persistence depends on interactions with other microbes , including resource competition (Mahowald et al, 2009), allelopathy (Leão et al, 2012) and cross-feeding (Rey et al, 2010). Fourth, colonizing microbes must survive potential host immune responses (Gomez and Balcazar, 2008;Maslowski and Mackay, 2011;Round et al, 2011;Carvaho et al, 2012;Hooper et al, 2012;Biswas and Kobayashi, 2013;Cebula et al, 2013;Robertson and Girardin, 2013;Bolnick et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Second, food intake and digestion rates affect the speed of food passage through the gut and thus the rate at which microbes are lost via excretion. Third, colonist persistence depends on interactions with other microbes , including resource competition (Mahowald et al, 2009), allelopathy (Leão et al, 2012) and cross-feeding (Rey et al, 2010). Fourth, colonizing microbes must survive potential host immune responses (Gomez and Balcazar, 2008;Maslowski and Mackay, 2011;Round et al, 2011;Carvaho et al, 2012;Hooper et al, 2012;Biswas and Kobayashi, 2013;Cebula et al, 2013;Robertson and Girardin, 2013;Bolnick et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence of several of these effects in the aquatic community. For example, Leão et al (2012) demonstrated, in a laboratory study, that substances produced by the LEGE 05292 strain of Oscillatoria sp. (portoamides A, B, C and D) had inhibitory effects on the growth of species of cyanobacteria, diatoms and green algae.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the toxin interferes with the metabolism of the seedlings (Saqrane et al, 2009), causing necroses (Chen et al, 2004, M-Hamvas et al, 2003. However, it should be noted that cyanobacteria produce several compounds other than cyanotoxins (Leão et al, 2012), the function of which is still unknown, as are their effects on plants. Although on aquatic community some organisms may suffer direct effects due to contact with these different compounds (Leão et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Algumas cianobactérias aparentam de fato possuir certa influência sobre a composição taxonômica de suas comunidades associadas, exercitando controle através de mecanismos de competição e de facilitação, como a liberação de carbono e nitrogênio fixados (BRAUER et al, 2015). Além disso, metabólitos secundários de efeito alelopático, incluindo inibidores de protease e bacteriocinas, podem ser liberados por diversas cianobactérias e essas moléculas poderiam, portanto, impactar a comunidade e atuar como agentes de seleção de micro-organismos (LEÃO et al, 2012b;SILVA-STENICO et al, 2011;SIVONEN, 2011 Interações entre cianobactérias e heterótrofos em consórcios, apesar de específicas a cada produtor primário, geralmente têm como padrão a troca mutualista de oxigênio e carbono, liberados pelas células cianobacterianas, por metabólitos produzidos por células heterotróficas, como nutrientes e vitaminas (COLE et al, 2014). Algumas análises transcritômicas fornecem suporte a essa observação, e também indicam que uma situação semelhante pode ser observada em relação ao nitrogênio fixado por cianobactérias diazotróficas em cocultivo com bactérias heterotróficas (BELIAEV et al, 2014).…”
Section: Cromossomos De Linhagens Identificadas No Gênerounclassified